Nanomaterial-Based Adsorbent: Promises, Opportunities, and Challenges to Develop Column Chromatography Radionuclide Generators for Nuclear Medicine. Issue 2 (3rd April 2017) - Dash, Ashutosh; Chakravarty, Rubel
Abstract : Although a wide range of separation techniques are used for preparation of radionuclide generators, the low pressure column chromatography technique has dominated the field significantly. In this technique, the adsorbent remains at the 'heart' of the system holding the parent radionuclide and this represents the cornerstone for its success. Although this strategy constitutes a successful paradigm for the preparation of radionuclide generators, the limited capacity of conventional adsorbents restricts their applicability for preparation of high activity generators while using low specific activity parent radionuclides. In this direction, the scope of using nanostructured materials in radionuclide generators represents an active area of research. This review is a comprehensive account of the latest research and development activities on the use of nanomaterial-based adsorbents in the development of radionuclide generators. It conveys the importance of nanomaterial-based-adsorbents, which can change the paradigm of radionuclide generator technology and stimulate further interest in the scientific community towards this field.